Sheeted Catfish Floss Production: Practical Innovation in Fish Floss Processing - Clara Saniya Margaretha; Fajar Nabil Nur Zhafir; Ghina Nur Amalia; Nur Wijayanti; Tabitha Mulia Tawadzu (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2023)
One of the processed fish that many people like is shredded fish. Choosing shredded fish is an alternative for consumers who don't like to consume meat. Fish also has protein with high nutritional value so it can be used as a source of protein to replace meat. Sheet floss is a processed food product made from catfish floss which is square in shape, brownish in color, hard in texture, and has a rough surface. This research was conducted in November-December 2023 on making shredded catfish sheets. To produce a recipe for shredded catfish sheets requires several production trials. The shredded catfish sheet product produced is in small sheets so it is easy to consume. Making shredded catfish sheets begins with making shredded catfish first. then make shredded sheets by baking. Shredded sheets have a brownish color due to the influence of added sugar, resulting in a Maillard reaction which causes a brownish color. slightly brownish in color. Then, the aroma produced by shredded sheets is not fishy because natural spices are used to eliminate the fishy smell. The taste of the shredded sheets is sweet and savory due to the addition of sugar and the use of spices which add a savory taste. The texture of these shredded sheets is rough, crisp and crunchy because the temperature and time when roasting the shredded shreds is controlled.